Lapisan Plasma Spray Ni-Al dan Al-Si Pada Tabung Baja Tahan Karat Austenitik Dengan Jarak Semprot Terbatas (Atmospheric Plasma Spray Coating of Ni-Al and Al-Si on Austenitic Stainless-Steel Tube with Limited Short Spray Distance) - Ahmad Sahid (Metalurgi, 2021)
Atmospheric Plasma Spray (APS) coating is a widely used thermal spray coating process in industrial applications. High density and high bond strength coating are the main features of this process that is required in almost coating properties for specific applications. The geometrical condition of the workpiece substrate dictates the parameter needed to achieve a certain quality of the coating. Changes in the geometry require modification on the parameter of the process to maintain the quality of the coating. Aluminum Silicon and Nickel Aluminum coating were applied on Stainless Steel substrate casing. Due to the limitation of spray distance between nozzle gun and substrate surface of the casing, modified several parameters of the process were taken. Several parameters were investigated to find out the optimum result of coating and verified with tensile bond strength test, hardness test, and microscopic analysis examination. These activities that involved modification of parameters, mechanical testing, and visual inspection informed that power as a function of voltage and ampere, powder feed rate, the surface speed of substrate (the particular amount of workpiece rotation per minute), and traverse speed of gun, contribute to the result of the optimum coating.